Assessment of Ventilated Athletic Uniforms for Improved Thermal Comfort. Issue 5 (September 2018) - McQuerry, Meredith; Hogans, Kristian
Due to disproportionate rates of American football players experiencing heat illness injuries and fatalities, there is a need to focus on the thermal comfort of athletes. Intolerance of internal metabolic heat production is a result of insufficient air flow in athletic uniforms. The application of clothing ventilation may significantly improve the thermal comfort of the athlete. Therefore, the purpose of this research was to investigate the thermal comfort of ventilated football uniforms based on ventilation type (traditional mesh versus laser micro-perforated). Ventilated football uniforms were evaluated for air permeability and subjective thermal comfort. Heart rate, perceived exertion, perceived comfort, and thermal sensation were collected during a human wear trial. Findings indicate differences in air permeability and thermal comfort perceptions between the ventilated uniforms.